2018
DOI: 10.1177/0143034318806546
|View full text |Cite
|
Sign up to set email alerts
|

A multi-component wellbeing programme for upper secondary students: Effects on wellbeing, buoyancy, and adaptability

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 39 publications
(42 reference statements)
0
28
0
Order By: Relevance
“…Moreover, processes such as self-efficacy, self-esteem, and mastery orientation, as well as the ability to manage anxiety, have been considered central to students' capacity to successfully navigate everyday struggles in school (Datu & Yuen, 2018). Each of these predictors represent malleable factors that can be targeted within classroom practices and interventions (Putwain et al, 2019), and the ability to bounce back following setbacks has been shown to be important in its own right, over and above the effects of academic coping (Putwain et al, 2012) or other constructs such as adaptability or prior motivation (Holliman et al, 2018).…”
Section: Buoyancymentioning
confidence: 99%
“…Moreover, processes such as self-efficacy, self-esteem, and mastery orientation, as well as the ability to manage anxiety, have been considered central to students' capacity to successfully navigate everyday struggles in school (Datu & Yuen, 2018). Each of these predictors represent malleable factors that can be targeted within classroom practices and interventions (Putwain et al, 2019), and the ability to bounce back following setbacks has been shown to be important in its own right, over and above the effects of academic coping (Putwain et al, 2012) or other constructs such as adaptability or prior motivation (Holliman et al, 2018).…”
Section: Buoyancymentioning
confidence: 99%
“…There is a growing body of evidence on academic buoyancy, traversing: (1) research differentiating buoyancy from other constructs (e.g., from coping, adaptability, grit, control, anxiety, and academic fear; Fong & Kim, 2019; Martin, Nejad, Colmar, & Liem, 2013; Putwain & Aveyard, 2018; Putwain, Chamberlain, Daly, & Sadreddini, 2014; Putwain, Daly, Chamberlain, & Sadreddini, 2015; Putwain et al, 2012; Putwain & Daly, 2013; Putwain et al, 2015; Symes, Putwain, & Remedios, 2015); (2) research on predictors of academic buoyancy (e.g., motivation predictors; Collie, Martin, Malmberg, Hall, & Ginns, 2015; Martin, Colmar, Davey, & Marsh, 2010; Martin & Marsh, 2006); (3) research on outcomes predicted by academic buoyancy (e.g., engagement; Martin, 2013; Martin & Marsh, 2008a); (4) intervention research targeting buoyancy (e.g., Puolakanaho et al, 2019; Putwain, Gallard, & Beaumont, 2019); and (5) research into buoyancy among different samples and contexts (e.g., cross-cultural comparisons; Collie et al, 2017; Datu & Yang, 2018; Martin, Yu, Ginns, & Papworth, 2017; Yun, Hiver, & Al-Hoorie, 2018).…”
Section: Academic Buoyancymentioning
confidence: 99%
“…There are significant applied benefits in demonstrating predictive validity of HERO constructs proposed in Psy-Cap theory in youth in terms of informing prevention and early intervention science, and potential application in educational contexts, which represent developmental equivalent of workplaces in which PsyCap theory has primarily been developed and tested. Moreover, the study and application of positively oriented strengths and capacities, aligns with goals of schools in which there is a significant focus on strengths-based approaches to student wellbeing [18][19][20].…”
Section: Introductionmentioning
confidence: 99%